Ludzka tożsamość wobec ekokolonializmu - Mamzer, Hanna (Człowiek i Społeczeństwo, 2017)
Contemporary reality of everyday functioning of postmodern humans, provokes deep changes in thinking of human identities and human relations it natural and cultural surroundings. Human sciences have to confront the fact, that it is no longer possible to divide human identities from those of non-humans. The connections between human and non-humans are clear and significant, and they are reflected on by the most prominent thinkers in the fields of social sciences (W. Kymlicka) and ecology (E.O. Wilson), at the same time. Understanding human identity requires connecting it with is natural surrounding, again. And this surrounding shall not be divided into “natural” and “cultural” ones anymore. Clarity of such divisions is seriously questioned by impossibility of drawing clear border lines between them. Such thinking creates new context for understanding humans. And this requires new tools as well: therefore it becomes very clear that humanities/social sciences and real science need to speak one voice.